2019
DOI: 10.1177/2047487319887835
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in VO2peak predicts readmissions for cardiovascular disease and mortality in patients undergoing cardiac rehabilitation

Abstract: Background Improvement in exercise capacity is a main goal of cardiac rehabilitation but the effects are often lost at long-term follow-up and thus also the benefits on prognosis. We assessed whether improvement in VO2peak during a cardiac rehabilitation programme predicts long-term prognosis. Methods and results We performed a retrospective analysis of 1561 cardiac patients completing cardiac rehabilitation in 2011–2017 in Copenhagen. Mean age was 63.6 (11) years, 74% were male and 84% had coronary artery dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 31 publications
3
51
0
2
Order By: Relevance
“…Only a few studies have examined the effect of change in CRF on clinical outcomes using the gold standard method of directly measured CRF by respiratory gas exchange analysis. Although there are methodological differences between studies, the findings of Mikkelsen et al 4 are consistent with those of Martin et al in coronary artery disease patients, 5 Bakker et al in chronic heart failure patients, 6 and population-based studies in apparently healthy adult men and women. [7][8][9] Similarly, many studies have demonstrated the importance of maintaining or improving CRF in reducing the risk of adverse clinical outcomes using indirect estimates of CRF.…”
Section: What Does This Study Add?supporting
confidence: 70%
See 1 more Smart Citation
“…Only a few studies have examined the effect of change in CRF on clinical outcomes using the gold standard method of directly measured CRF by respiratory gas exchange analysis. Although there are methodological differences between studies, the findings of Mikkelsen et al 4 are consistent with those of Martin et al in coronary artery disease patients, 5 Bakker et al in chronic heart failure patients, 6 and population-based studies in apparently healthy adult men and women. [7][8][9] Similarly, many studies have demonstrated the importance of maintaining or improving CRF in reducing the risk of adverse clinical outcomes using indirect estimates of CRF.…”
Section: What Does This Study Add?supporting
confidence: 70%
“…Mikkelsen et al demonstrated that directly measured peak VO 2 as well as a change in peak VO 2 over time were highly predictive of risk for future readmissions for CVD and all-cause mortality in a large cohort of CVD patients undergoing cardiac rehabilitation. 4 Importantly, the prognostic power of the change in peak VO 2 with serial testing was independent of baseline peak VO 2 and clinical history.…”
Section: What Does This Study Add?mentioning
confidence: 96%
“…Increasing functional capacity is important to improve healthy life expectancy and reduce hospital readmissions [ 3 ]. Maintaining the ability to perform activities of daily living (ADLs) is also associated with favorable prognosis in older HF patients [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exercise capacity, which is assessed based on peak oxygen uptake (peak VO 2 ), is considered the gold standard for assessing aerobic exercise intensity and is generally used in formulating a safe, effective, and individualized exercise prescription for CR and return to work and daily activity recommendations [ [15] , [16] , [17] ]. Peak VO 2 is highly related to morbidity and mortality in CVD populations [ [18] , [19] , [20] ]. Furthermore, Peak VO 2 was also expressed as metabolic equivalent (MET, 1 MET = 3.5 ml⋅kg −1 ⋅min −1 VO 2 ).…”
Section: Introductionmentioning
confidence: 99%